The effects of intravenous tramadol vs. intravenous ketamine in the prevention of shivering during spinal anesthesia: A meta-analysis of randomized controlled trials - Fenta, Efrem; Kibret, Simegnew; Hunie, Metages; Tamire, Tadese; Fentie, Yewlsew; Seid, Shimelis; Teshome, Diriba (Frontiers in Medicine, 2022)
Background: Shivering is a common complication after subarachnoid administration of local anesthetics. Intravenous ketamine and tramadol are widely available anti-shivering drugs, especially in developing settings. This meta-analysis aimed to compare the effects of intravenous ketamine versus tramadol for post-spinal anesthesia shivering. Materials and Methods: PubMed/MEDLINE, Web of Science, Cochrane Library, Embase, and Google Scholar databases were used to search for relevant articles for this study. Mean difference (MD) with 95% confidence interval (CI) was used to analyze continuous outcomes, and risk ratio (RR) with 95% CI to analyze categorical results. The heterogeneity of the included studies was assessed using the I2 test. We utilized Review Manager 5.4.1 to perform statistical analysis. Results: Thirteen studies involving 1532 patients were included in this meta-analysis. Ketamine had comparable effects in preventing post-spinal anesthetics shivering (RR =1.06; 95% CI [0.94, 1.20], P = 0.33, I2 = 77), and onset of shivering ((MD = -0.10; 95%CI [− 2.68, 2.48, P = 0.94, I2 = 0%), lower incidences of nausea and vomiting (RR = 0.51; 95%CI [0.26, 0.99], P = 0.05, I2 = 67%), and lower incidences of bradycardia (RR = 0.16; 95%CI [0.05, 0.47], P = 0.001, I2 = 33%), higher incidence of hallucinations (RR = 12; 95%CI [1.58, 91.40], P = 0.02, I2 = 0%), and comparable effects regarding the incidences of hypotension (RR = 0.60; 95%CI [0.30, 1.21], P = 0.15, I2 = 54%) as compared to tramadol. Conclusions: Intravenous ketamine and tramadol are comparable in the prevention of post-spinal anesthetic shivering. Ketamine had a better outcome with less occurrences of nausea, vomiting, and bradycardia. However, ketamine was associated with higher incidences of hallucinations than tramadol.